PENGEMBANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMA PERGURUAN SETIA BUDI ABADI PERBAUNGAN - Damanik, Erikson (Politeknik Bisnis Indonesia, 2018)
Private College Foundation Setia Budi Abadi Perbaungan is a legal entity engaged in education that aims to educate the life of the nation. In achieving that goal, Setia Budi Abadi Perbaungan Private College Foundation still uses procedures and processes that are still considered inadequate to handle the academic processes that take place in the current area of ​​globalization. For this reason, it is necessary to develop a Web-based Information System that is able to assist in the process of academic activities at the Foundation Setia Budi Abadi School. The analysis carried out included problem analysis, analysis of input and output documents. After that, identification of new system requirements, interviews and observations was carried out. Design system proposals include process design with Data Flow Diagrams (DFD), input and output using Page Hypertext Processing (PHP), us data and MySQL. The methodology used in developing information systems in this final project is the System Development Life Cycle (SDLC).The results of this final project are in the form of a proposed system design that can be applied to assist the academic process at the school